45S5 Bioglass®–MWCNT composite: processing and bioactivity - Porwal, Harshit; Estili, Mehdi; Grünewald, Alina; Grasso, Salvatore; Detsch, Rainer; Hu, Chunfeng; Sakka, Yoshio; Boccaccini, Aldo R.; Reece, Mike J. (Journal of Materials Science: Materials in Medicine, 2015)
Multi-walled carbon nanotube (MWCNT)–Bioglass (BG) matrix composite was fabricated using a facile and scalable aqueous colloidal processing method without using any surfactants followed by spark plasma sintering (SPS) consolidation. The individual MWCNTs were initially uniformly dispersed in water and then entirely immobilized on the BG particles during the colloidal processing, avoiding their common re-agglomeration during the water-removal and drying step, which guaranteed their uniform dispersion within the dense BG matrix after the consolidation process. SPS was used as a fast sintering technique to minimise any damage to the MWCNT structure during the high-temperature consolidation process. The electrical conductivity of BG increased by 8 orders of magnitude with the addition of 6.35 wt% of MWCNTs compared to pure BG. Short-duration tests were used in the present study as a preliminary evaluation to understand the effect of incorporating MWCNTs on osteoblast-like cells. The analysed cell proliferation, viability and phenotype expression of MG-63 cells showed inhibition on 45S5 Bioglass®–MWCNT composite surfaces.